The notion of 'living together' and the reservations of dissenting judges of the European Court of Human Rights: a short reflection$h - Durante, Milena (Il diritto ecclesiastico, 2024)
Between 2014 and 2017, the European Court of Human Rights was seised of some important appeals in the field of religious clothing and specifically the longstanding issue of the wearing of the veil. Among these, the most significant case is represented by the SAS v. France affair, which questioned the legitimacy of the French law c.d. ‘anti-burqa’. To note in the debate developed around the judging case were the discordant opinions on the use of the notion of ‘living together’. While, on the one hand, the majority of the judges of the Court identify in the guarantee of living together a legitimate purpose to be pursued, on the other, the dissenting judges have expressed strong reservations about this approach. The hope is that the positions supported by dissenters can contribute to the identification of an alternative way in terms of external manifestations of religious sentiment ; a solution, therefore, that considers the tension that exists today between the tendency to universality and the protection of particularity, between the demands of peaceful coexistence and the protection of the rights of minorities. What we will try to do is to verify if it is possible to find in dissenting opinions, or in the dialogue between the majority and the minority opinions, strategies that can mitigate that secularism ‘on the defensive’ who prefers a public space completely immune from the religious, to pursue which adopts increasingly accentuated forms of compression of the private sphere of the individual.